2005
DOI: 10.2174/1568007054038184
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Associated Proteins in Alzheimers and Prion Disease

Abstract: Clustering of activated microglia in Abeta deposits is related to accumulation of amyloid associated factors and precedes the neurodegenerative changes in AD. Microglia-derived pro-inflammatory cytokines are suggested to be the driving force in AD pathology. Inflammation-related proteins, including complement factors, acute-phase proteins, pro-inflammatory cytokines, that normally are locally produced at low levels, are increasingly synthesized in Alzheimer's disease (AD) brain. Similar to AD, in prion disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 107 publications
(176 reference statements)
1
53
0
1
Order By: Relevance
“…Despite the increased synthesis of SAP in AD brains as shown by McGeer et al [31] , we were unable to detect an increase in CSF SAP levels in AD and MCI cases compared to controls [31] . Possibly CSF SAP levels are not only dependent on the intraparenchymal synthesis, but also on accumulation in A ␤ plaques [17,19] and diffusion or transport across the blood-brain barrier; a subject for further study. Only three cross-sectional studies investigating CSF SAP levels in AD and controls have been reported (as summarized in table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the increased synthesis of SAP in AD brains as shown by McGeer et al [31] , we were unable to detect an increase in CSF SAP levels in AD and MCI cases compared to controls [31] . Possibly CSF SAP levels are not only dependent on the intraparenchymal synthesis, but also on accumulation in A ␤ plaques [17,19] and diffusion or transport across the blood-brain barrier; a subject for further study. Only three cross-sectional studies investigating CSF SAP levels in AD and controls have been reported (as summarized in table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…SAP binding to newly formed amyloid fibrils may protect the A ␤ deposits from proteolysis, and as a consequence promote A ␤ fibril and amyloid plaque formation in the brain [11,[13][14][15][16] . Clustering of activated microglial cells in A ␤ plaques was observed in SAP-and C1q-containing A ␤ plaques preceding tau-related neurodegenerative changes [17] . In vitro, SAP and C1q inhibit the microglial uptake of A ␤ [18] .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since AD and PRE share analogous clinical and neuropathological characteristics (Aguzzi and Haass 2003;Veerhuis et al 2005;Barnham et al 2006), in the present work, we perform a comparative study, using Ab and PrP synthetic peptides in order to determine the involvement of Cdk5 in tau phosphorylation and neuronal death under AD and PRE conditions. Using the selective Cdk5 inhibitor roscovitine, we observed that, when Cdk5 is not active, there is a significant reduction in the neuronal apoptotic death caused by PrP 106-126 or Ab 1-40 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the PrPC and physiopathological mechanisms of Alzheimer's disease (AD) is well understood [23][24][25][26][27][28][29]. On our part, we have observed a particular behaviour of PrPC in brains with AD.…”
Section: Introductionmentioning
confidence: 69%